Astronomy and Literature | Canon and Stylometrics (Interfaces: A Journal of Medieval European Literatures, 2021)
This eighth issue of Interfaces contains two thematic clusters: the first cluster, entitled The Astronomical Imagination in Literature through the Ages, is edited by Dale Kedwards; the second cluster, entitled Medieval Authorship and Canonicity in the Digital Age, is edited by Jeroen De Gussem and Jeroen Deploige.
Keywords: Europe; Middle Ages; Medieval Literature; Comparative Litarature; Astronomy; Stylometrics